Depositional processes and the formation of the paleontological and archeological record at the Lagoa dos Porcos site, Southeastern Piaui - Macedo, Andréia Oliveira; Felice, Gisele Daltrini; Corrêa, Antonio Carlos de Barros (Revista Brasileira de Geomorfologia, 2025)
This article addresses the processes involved in the formation of Quaternary sedimentary deposits at the Lagoa dos Porcos site, with emphasis on stratigraphic analysis, with the aim of providing new contributions on the depositional processes involved in the formation of the paleontological and archaeological record of this shallow lake, located in the Serra da Capivara Archaeological Area, in the semi-arid region of Piauí. The research method used a combination of granulometric analysis, verification of morphological properties, radiocarbon dating (AMS) and optically stimulated luminescence (OSL) in samples of sediments and carbonate nodules from stratigraphic profile 4. The data obtained indicate that the lake holds information reflecting at least four periods of deposition related to the Pleistocene, the Pleistocene/Holocene transition, and the early and recent Holocene. Regarding the source area of ​​the paleofauna bones and archaeological material, it is proposed that they came from the surrounding areas, such as the pediment ramps and ancient terraces.